2022
DOI: 10.3390/ijerph192214701
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Burnout in Healthcare Professionals

Abstract: Burnout in healthcare professionals remains an ongoing concern. There are a number of variables associated with reactivity to stress in healthcare staff. This study wants to identify risk factors which predispose healthcare professionals to burnout. Material and Methods: The cross-sectional study included a group of 200 subjects, medical staff and auxiliary staff from the national health units, who gave their free consent to answer the questions regarding the level of perceived stress at work. The screening to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…24 Other pre-COVID-19 studies suggested that in large cities, income is lower in relation to higher living costs, increased traffic and increased competition in the field of activity, and that this may explain those differences in medical personnel burnout between rural and urban areas. 22 , 25 Although the lack of resources and increased case-load in rural and semi-rural areas have been hypothesised as risk factors for burnout, the present study and findings from previous research do not support this. Other factors previously reported in the literatures need to be investigated as possible protective factors for burnout.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…24 Other pre-COVID-19 studies suggested that in large cities, income is lower in relation to higher living costs, increased traffic and increased competition in the field of activity, and that this may explain those differences in medical personnel burnout between rural and urban areas. 22 , 25 Although the lack of resources and increased case-load in rural and semi-rural areas have been hypothesised as risk factors for burnout, the present study and findings from previous research do not support this. Other factors previously reported in the literatures need to be investigated as possible protective factors for burnout.…”
Section: Discussioncontrasting
confidence: 99%
“…A more recent study from Romania showed no difference in burnout rates between rural and urban areas. 22 Previous work has also suggested a higher rate of burnout among rural mental health providers, attributed to factors such as limited resources, geographical isolation, difficulties with recruitment and retention, and a tendency for rural dwellers to delay help-seeking and present later in their course of illness. 23 …”
Section: Discussionmentioning
confidence: 99%
“…There are contradictory data on the connection between relationship status and sensitivity to burnout. 49 , 50 …”
Section: Discussionmentioning
confidence: 99%
“…Shanafelt and colleagues found that providing clinicians with 20% of the time to do "what they most care about" is associated with 50% less burnout [9]. In addition, another study presents the high chances of developing burnout syndrome in female resident doctors who work more than 80 hours a week, regardless of their specialization [10].…”
Section: Figure 1: the Vicious Cycle Representing The Consequences Of...mentioning
confidence: 99%